Penerapan Building Information Modelling (BIM) oleh PT PP (Persero) Tbk pada Proyek Jembatan di Indonesia - Sarifah, Fitriana; Kadapi, Muhamad; Nurhalimah, Alisya Kurnia; Firdaus, Ridwan; Ropiq, Reina Aenur; Nugraha, Melyk; Putra, Mochammad Gilang Riana (Universitas Batanghari, 2024)
Bridge that implement BIM can increase planning accuracy, reduce construction risks, and better plan the entire project. PTPP is a pioneer contractor that has implemented BIM in Indonesia since the end of 2015. The PTPP division that handles road and bridge infrastructure is Infrastructure 1. The aim of this research is to evaluate whether the BIM implementation is commonly carried out on PTPP bridge projects. The aim of this research is to evaluate the BIM implementation to the bridge project. This research method was used library research with a focus on the use of valid literature that already has previous research. The result of this research is that the BIM implementation to PTPP bridge projects is commonly used. All PTPP bridge projects since the end of 2015, a total of 3 projects have implemented BIM. Two bridge projects, Kendari Bay Bridge and the PIK 2 Connecting Bridge, North Jakarta, provide information about the implementation of BIM which can be accessed by the public via the official PTPP website and social media. Information on BIM implementation includes the process, software used, and the benefits on the bridge project. Meanwhile, for the Bogeg Bridge, Serang, no detailed information is available regarding the application of BIM. For the Kendari Bay Bridge project, the benefit of implementing BIM is that PTPP designed the bridge in just one month, saving three months. 3D model visualization really helps minimize errors and save time during the actual construction phase so that teams can collaborate easily using the same 3D model throughout the project. For the PIK 2 Bridge project, the benefits of implementing BIM include synchronous work drawings, helping with volume calculations, speeding up topographic surveis, detecting discrepancies, visualizing the project implementation schedule, helping coordinate with the project team, and helping with quality checks in the field.